Diffusion‐weighted imaging for evaluation of uterine arterial embolization of fibroids. Issue 6 (25th February 2013) - Faye, Nathalie; Pellerin, Olivier; Thiam, Rokhaya; Chammings, Foucauld; Brisa, Marie; Marques, Enio; Cuénod, Charles A.; Sapoval, Marc; Fournier, Laure S.
<x xml:space="preserve">Abstract</x> Purpose To determine whether diffusion‐weighted imaging (DWI) characteristics could predict the effectiveness of uterine arterial embolization in treatment of fibroids. Methods This retrospective study included 17 women (27 fibroids) who underwent uterine arterial embolization for fibroids. MR imaging (1.5 T) was performed before, 1 week and 6 months after uterine arterial embolization. The volume, T2 signal, T1 signal, enhancement after contrast media injection, DWI signal (b = 500 s/mm2) and apparent diffusion coefficient (ADC) were assessed for fibroids. Results DWI signal or ADC, whether before or 1 week after the procedure, did not show a statistical relationship to success of uterine arterial embolization. On the 1‐week follow‐up, 22% of fibroids enhanced vs. 85% on baseline, P < 0.0001 and DW signal intensity increased. ADC values in fibroids decreased between baseline and 1‐week (1.61 vs. 1.53 × 10−3 mm2/s, P = 0.13). On 6‐months, ADC continued to decrease compared with baseline (1.27 × 10−3 mm2/s, P = 0.002), but with a lower signal on DWI. No changes were observed in myometrium ADC at any time point. Conclusion Our study demonstrated that DWI and ADC reflected early and delayed changes in fibroids after embolization; however, we were not able to demonstrate a statistically significant relationship with outcome. Magn Reson Med 70:1739–1747, 2013. © 2013 Wiley Periodicals, Inc.